Estratégia de educação em saúde online no período perinatal durante a pandemia da COVID-19: experiência das mulheres - Silva, Katia Gomes da (Universidade Federal de São Carlos, 2022)
The quality of women's perinatal period experience has been globally disseminated for years given its impact on the course of life for them, their children and society. Considering the COVID-19 pandemic scenario since the beginning of 2020, the speed of its spread and its severity on some people, among them pregnant and postpartum women, it was necessary changes in practices and policies in all health sectors, thus, influencing women's experiences during pregnancy, childbirth and postpartum. Aim: To analyze the impact of online health educational strategy in the pregnant and postpartum women’s autonomy and satisfaction during the COVID-19 pandemic. Methods: Exploratory and descriptive study with qualitative approach using Bardin's thematic analysis. The study population consisted of 13 women who participated in the extension project "Support Group for healthy pregnancy, childbirth and postpartum", respecting ethical precepts. The online focus group was used for data collection. Results: Three thematic categories were identified “Information and displacements”; “Transposing the cesarean”; and “Welcoming and well-being made the difference". Conclusions: The study demonstrated that the intervention had a positive impact on women during the perinatal period and contributed to a positive experience during pregnancy, childbirth, postpartum and mothering, in addition to promoting the autonomy of the participants.
Online health education strategy in the perinatal period during the COVID-19 pandemic: women's experience
Keywords: Gravidez; Educação em saúde; Autonomia pessoal; Satisfação do paciente; COVID-19; Pregnancy; Health education; Personal autonomy; Patient satisfaction; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM OBSTETRICA